Detection the ability of Uropathogenic bacteria to produce Biofilm andEvaluation the Screening methods - عبد الجليل إبراهيم, علا (University of Thi-Qar Journal of Science, 2016)
twenty urine samples were collected from patients have acute inflammation of the urinary tract withkidney sands . three types of bacteria were isolated from samples. it was found that the main causativeagent for 85% of these conditions due to E.coli while the remaining ones belongs to Pseudomonasaeruginosa and Klebsiella pneumoniae. to detect the ability of these isolates to form biofilm . twodifferent methods were used , the first method is tube method (TM) showed that E. coli possesseshigh effectiveness of biofilm formation in the glass as well as Pseudomonas aeruginosa while thebacterium Klebsiella pneumoniae able to form biofilm moderately. It was observed when using thesecond method Congo red method (CRA) that all isolates composed biofilm when cultured on CRAexcept 5% of isolates belongs to bacterium Pseudomonas aeruginosa was negative for this test, . thefirst method is more accurate than the other to show the degree of biofilm formation to the naked eye, and both methods are considered qualitative not quantitative. The present study aims to investigate theability of bacteria isolated from people with frequent urinary tract infections UTI associated withkidney stones on biofilm production .